Anticancer Potential of Albumin Bound Wnt/β‐Catenin Pathway Inhibitor Niclosamide in Breast Cancer Cells. Issue 29 (11th August 2021) - Ari, Ferda; Erkisa, Merve; Pekel, Gonca; Erturk, Elif; Buyukkoroglu, Gulay; Ulukaya, Engin
Abstract: Albumin‐based nanoparticle transport systems (nab‐technology) are a new strategy in cancer treatment and we aimed to increase the effectiveness of Niclosamide using this technology. Niclosamide was bound with bovine serum albumin (BSA) by desolvation to yield nanoparticle albumin‐bound Niclosamide (nab‐Niclo). Nab‐Niclo anticancer activity was assessed by proliferation, apoptosis and DNA damage analyses on breast cancer cells. The results implied that nab‐Niclo was a more potent agent in the inhibition of cell viability than free Niclosamide and albumin. Flow cytometry analysis show that nab‐Niclo triggered apoptosis by caspase and mitochondria‐dependent pathways in cells and nab‐Niclo enhances apoptosis by induce DNA damage in cells. Overall results of this study showed that the nanoparticle form of Niclosamide is effective for breast cancer treatment, presenting a new treatment strategy that can be safe and effective for breast cancer patients. Abstract : This study shows that albumin‐bound form of Niclosamide (nab‐Niclo) inhibits breast cancer cell viability, induces apoptosis, mitochondrial depolarization, and oxidative stress with DNA damage. Also, it appears to be more effective than niclosamide alone. nab‐Niclo may be a potential agent for breast cancer treatment.